ACUTE EXPOSURE TO ARSENITE INDUCES METALLOTHIONEIN ISOFORM-SPECIFIC GENE EXPRESSION IN HUMAN PROXIMAL TUBULE CELLS - Garrett, Scott H.; Belcastro, Marycharmain; Sens, Mary Ann; Somji, Seema; Sens, Donald A. (Journal of Toxicology and Environmental Health, Part A, 2001)
The expression of metallothionein (MT) mRNA and protein was determined in human proximal tubule cells (HPT) following acute exposure to the classic stimulators of the stress response, heat and sodium arsenite (As 3+ ). Treatment of the cells with 100 µ M As 3+ for 4 h resulted in a significant increase in the MT-1 and MT-2 proteins immediately preceding and following removal of the stress. The level of the MT-3 isoform protein was unchanged as a result of As 3+ treatment. An analysis of the MT isoform-specific mRNA demonstrated that control cells express the MT-1E, MT-1F, MT-1X, MT-2A, and MT-3 genes, but not the MT-1A, MT-1B, MT-1G, MT-1H, and MT-4 genes. Treatment with As 3+ resulted in a significant increase in the expression of the MT-1X gene and appearance of mRNA for the MT-1A gene. Expression of the other MT genes was unaffected by As 3+ exposure, except one isolate expressed a low level of MT-1G mRNA at several time points. It is likely that the increase in MT protein seen in As 3+ -treated cells is due to the increased expression of the MT-1X gene because its expression is much greater than the MT-1A isoform. Treatment of the HPT cells with heat shock had no marked effect on the levels of MT protein or mRNA. This study demonstrates that acute exposure to As 3+ increases the levels of MT protein and that this elevation most likely arises from increased expression of the MT-1X isoform.